(untitled) (Pedagogy of Higher and Secondary Education, 2013)
Testsova A. A. Herbert Spencer – founder reform pedagogy. Article revealing a characteristic feature of the famous English scientist and philosopher Herbert Spencer, as one of the ideological founders of progressive educational. In particular, the position of the principle of freedom in its educational system.